The impact of the Bologna Reform on student outcomes - Benedikt Siegler; Bernhard Enzi (Ludwig-Maximilians-Universität München, Volkswirtschaftliche Fakultät, 2016)
How did the introduction of the Bachelor-degree system affect students in Germany? Combining rich data on university students with administrative data on universities' study programs, we exploit variation in the timing of Bachelor-degree implementation across departments. To account for endogeneity in students' enrollment decisions, we apply an instrumental-variable approach based on the distance differential between an individual's nearest universities with a Bachelor's and a traditional degree program. Overall, we do not find reform effects on students' mobility, drop out, and internship participation, although there is indication that the reform reduced drop out for females and for high-achieving students and increased study satisfaction.
urn:nbn:de:bvb:19-epub-29635-0
Keywords: I28; I21; H75; 330; Bologna Reform; Bachelor introduction; student outcomes; instrumental variables